VIKSIT BHARAT 2047: A JOURNEY TOWARDS INDIA'S FUTURE - Patel, Vipin; Kumar, Rohit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Vikshit Bharat, or Developed India, stands as a visionary endeavor to foster comprehensive socio-economic advancement in India by the occasion of its centenary of independence in 2047. This article navigates the complexities of achieving this vision, examining challenges and opportunities across sectors. India aims to attain a $30 trillion economy, ensure every citizen has access to water and housing, equip cultivators with drones to empower them, expand the availability of affordable medications through Jan Aushadhi Kendras, and implement green and sustainable growth policies, following this vision. By synthesizing empirical evidence, theoretical insights, and policy recommendations, this research contributes to the scholarly discourse on nation-building. It offers actionable insights for policymakers, practitioners, and researchers committed to shaping India's trajectory towards 2047 and beyond.